THE SENTENCE PRODUCTION OF SLOW LEARNERS AND ITS IMPLICATION ON LEARNING: A CASE STUDY AT SDI MELATI NUSANTARA - Wardatul Yunita Tikasari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
Slow learner children have barriers in complex thinking processe especially in language. Low IQ levels craft them difficulties to identify sentence structure which result in the disruption of their sentence production process. Also, these difficulties interfere their communication in learning process. This study aimed to present an overview of slow learners’ sentence production and its implications in learning. This research was descriptive qualitative research with interactive model analysis techniques. Data were collected through an observation of the students’ learning activities and in-depth interviews with shadow teachers and the principals. The results indicated that slow learners produced simple sentences like verbal sentences, nominal sentences, adjectival sentences, and prepositional sentences in forms of declarative, imperative, and interrogative types. Moreover, the schools had adjusted the learning components, such as the objectives, conditions, materials, and evaluations, to the learning process of slow learners at schools. One of its applications was a semi-separated class system, using interactive videos as a learning media, using companion books, and adjusting the evaluation of the learning system.